2020
DOI: 10.1136/archdischild-2020-320972
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of reviews of symptoms and signs of COVID-19 in children and adolescents

Abstract: ObjectiveTo undertake a systematic review of reviews of the prevalence of symptoms and signs of COVID-19 in those aged under 20 years.DesignNarrative systematic review of reviews. PubMed, medRxiv, Europe PMC and COVID-19 Living Evidence Database were searched on 9 October 2020.SettingAll settings, including hospitalised and community settings.PatientsChildren and young people (CYP) under age 20 years with laboratory-proven COVID-19.Study review, data extraction and qualityPotentially eligible articles were rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
110
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 32 publications
13
110
2
5
Order By: Relevance
“…Among the younger children, gastrointestinal rather than respiratory complaints predominated, which may be a factor explaining why only one had been tested for covid-19 before death. The preponderance of gastrointestinal symptoms among children with covid-19 has been described previously 31323334. Such symptoms may occur as part of a broader constellation of complaints that may include respiratory symptoms in isolation or as part of the multisystem inflammatory disorder that has been identified as a rare complication of covid-19 in children.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among the younger children, gastrointestinal rather than respiratory complaints predominated, which may be a factor explaining why only one had been tested for covid-19 before death. The preponderance of gastrointestinal symptoms among children with covid-19 has been described previously 31323334. Such symptoms may occur as part of a broader constellation of complaints that may include respiratory symptoms in isolation or as part of the multisystem inflammatory disorder that has been identified as a rare complication of covid-19 in children.…”
Section: Discussionmentioning
confidence: 94%
“…The preponderance of gastrointestinal symptoms among children with covid-19 has been described previously. 31 32 33 34 Such symptoms may occur as part of a broader constellation of complaints that may include respiratory symptoms in isolation or as part of the multisystem inflammatory disorder that has been identified as a rare complication of covid-19 in children. In its November 2020 update, the American Academy of Pediatrics reported that children accounted for between 0.00% and 0.23% of all covid-19 related deaths in the US, with 17 states reporting no deaths in children.…”
Section: Discussionmentioning
confidence: 99%
“…Cough and fever were globally regarded as main factors in previous studies [76,77]. The symptoms could be found in children, adolescents, and adults [78] in research on Europe [79], the UK [80], the United States [81], and other countries. Considering dyspnoea, infection with COVID-19 could result in severe outcomes and death from pneumonia with severe symptoms [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…23 Neutralizing antibodies at a 50% inhibitory dilution (ID50) were detected in 56 of 69 (81%) serum samples collected during acute infection, 53 of 56 (95%) samples collected 2 months after acute infection, and 47 of 50 (94%) of samples collected 4 months after acute infection (Figure 2). Acute infection samples for which there was no appreciable neutralizing activity were collected earlier after symptom onset or SARS-CoV-2 diagnosis than acute infection samples with detectable neutralizing antibodies [median (IQR) of 7 (5,8) vs. 9 (7, 13) days; p=0.01]. Between acute infection and 2 months after acute infection, levels of neutralizing antibodies declined in 31 (55%) children, increased in 24 (43%) children, were stable in one (2%) child (median ID50: 577 vs. 379; p=0.04).…”
Section: Sars-cov-2-infected Children and Adolescents Generate Durable Neutralizing Antibody Responsesmentioning
confidence: 99%
“…Epidemiological data from around the world indicate that children and adolescents with SARS-CoV-2 infection typically have milder illness courses than adults. [6][7][8] Notably, SARS-CoV-2 infection in children and adolescents is often asymptomatic or associated with such minor symptoms that children infrequently come to medical attention. 9,10 The varied clinical manifestations of SARS-CoV-2 infection among children and adults suggest that age may modify the host response to SARS-CoV-2, as has previously been demonstrated for several other viruses.…”
Section: Introductionmentioning
confidence: 99%